A rare case of giant cell lung carcinoma with intracardiac extension via the pulmonary vein and thrombus formation. Issue 6 (25th June 2018) - Leivaditis, Vasileios; Koletsis, Efstatios; Spiliotopoulos, Konstantinos; Grapatsas, Konstantinos; Tzelepi, Vasiliki; Dougenis, Dimitrios
Abstract: A 61-year-old man presented with dyspnea, left thoracic pain and productive cough. Chest computed tomography demonstrated a solid mass of the left upper lobe, 2.9 × 1.8 cm 2 in size, which had irregular borders and appeared to infiltrate and totally occlude the upper left pulmonary vein extending up to the left atrium (LA) with thrombus formation. The patient underwent median sternotomy and left pneumonectomy, combined with LA thrombus resection under cardiopulmonary bypass (CPB) with bicaval cannulation. The LA was partially resected and the intracavitary thrombus was completely removed. The surgical margins were free of tumor cells. Episodes of embolism were not observed during surgery. The patient was successfully weaned from CPB. The postoperative course was uncomplicated. Pathological examination of the resected specimen revealed giant cell carcinoma.